An Alternative for All-Electric Ships Applications: The Synchronous Reluctance Motor. (10th March 2013) - Proimadis, Ioannis Ch.; Spyropoulos, Dionysios V.; Mitronikas, Epaminondas D.
Abstract : The three-phase synchronous reluctance motor (SynRM) is presented as a possible alternative in all-electric ship applications. The basic features of this motor with regard to the other types of motors are shown. The structure of the motor and specifically the structure of its rotor are analyzed, while the basic operating principles are presented and references on commonly used control strategies are made. In this paper, a demonstration of a reluctance motor fed by a voltage source inverter (VSI) takes place. To demonstrate the operation of the motor fed by a VSI, an example using a scalar control method is implemented, where harmonic injection PWM (HIPWM) is used to drive the VSI. Experimental results on a commercially available motor are shown, focusing on the harmonic content of the current.